PELATIHAN MENGKEMAS PAKET AGROWISATA BAGI ANGGOTA KELOMPOK TANI DI DESA KERTA, KECAMATAN PAYANGAN, KABUPATEN GIANYAR - IP SUDANA; NP EKA MAHADEWI (Buletin Udayana Mengabdi, 2015)
The development of agro-tourism potential in the village of Kerta are appropriately done by introducing themto travelers. This was done in order that farming communities receive economic benefits, such as the availabilityof additional jobs and to increase sales of agricultural products, especially in the form of citrus and floral crops.Efforts that can be taken is a manufacture of innovative agro-tourism packages in order to attract the number oftourists visiting the village of Kerta and improving the quality of human resources. In order to develop furtherKerta village, devoteed Team has successfully trained farmer groups in making tour package entitled ”Bali OrganicFarming Activities” meaning that tourist activity to recognize various types of plants. Apart from this, the farmersobtained benefits and watch the activity of farmers and directly involved in managing land in plantation farmergroups Sekar Bumi and farmer groups Teak Bloom. The agro-tourism activities that take tourists to cultivate andreap immediate agricultural products to be processed into the local cuisine of Bali (Balinese Cooking Experience).The second package is already manifested in the form of brochures.Keywords: agro-tourism, tour package and Bali Organic Farming Activities